Dancers connect with Shuler audience - Barnes, Rebecca (Raton, NM Raton Range, 1993)
It is a review of a performance by the Ririe-Woodbury Dance Company at the Shuler Theater.
Newspaper Article
Master list item #: 32
File location is in the Raton file Cabinet
Keywords: Pearson, Jerry -- Choreographer; Moulton, Lisa Ford -- Dancer; Johnson, Keith -- Dancer; Haws, Janice -- Dancer; Ririe-Woodbury Dance Company -- Dance Troupe; Dance Performance; Performance Reviews; Shuler Theater; Raton, New Mexico